Accuracy of Various Doses of Sulphate Acid (H2SO4) in early Pregnancy Detection in Friesian Holstein Dairy Cows - Setiawati, Euis Nia; Saleh, Dadang Mulyadi; Armelia, Vony; Nugroho, Aras Prasetya (International Journal of Forest, Animal and Fisheries Research, 2021)
This study aims to find out the accuracy of doses and time in early detection of pregnancy using sulfuric acid (H2SO4) concentrated in FH dairy cows. A total of 600 urine samples came from 120 FH dairy cows that had been artificially inseminated on the 24th day, the 34th day, the 44th day, the 60th day. Urine samples are taken in the morning from 06.00 – 10.00. Concentrated doses of Sulphate Acid (H2SO4) are divided into 3 including P1 (0.1 ml), P2 (0.5 ml) and P3 (1.0 ml) according to treatment. The observed variables are gas fluorescence in the solution, discoloration of the limes pink solution, and the timing of changes in the solution. To ensure the pregnancy is carried out rectal palpation examination day 60 after artificial insemination. The collected data is analyzed with the Chi-Square test. Chi-Square test analyst results showed that sulphate acid (H2SO4) dose treatment is no different (P >0.05) in detecting early development. The optimal dose of use of Sulphate Acid (H2SO4) concentrated in detecting early production of friesian holstein milk cows of age is achieved at a dose of 0.5 ml with an accuracy of 83.33 % - 95.23 %, which indicated the formation of air bubbles (fluorensce) and pink in the duration of time, with a duration of 9-45 seconds. Conclusion Early pregnancy detection technology method "Concentrated Sulphate Acid (H2SO4) can be used to detect cow pregnancy 24 days after insemination.